Microbiota-Specific CD4CD8αα Tregs: Role in Intestinal Immune Homeostasis and Implications for IBD - Sarrabayrouse, Guillaume; Alameddine, Joudy; Altare, Frédéric; Jotereau, Francine (Frontiers in Immunology, 2015)
In studies in murine models, active suppression by IL-10-secreting Foxp3 regulatory T cells (Tregs) has emerged as an essential mechanism in colon homeostasis. However, the role of the equivalent subset in humans remains unclear, leading to suggestions that other subsets and/or mechanisms may substitute for Foxp3 Tregs in the maintenance of colon homeostasis. We recently described a new subset of CD4CD8αα T cells reactive to the gut bacterium Faecalibacterium prausnitzii and endowed with regulatory/suppressive functions. This subset is abundant in the healthy colonic mucosa, but less common in that of patients with irritable bowel disease (IBD). We discuss here the physiological significance and potential role of these Tregs in preventing inflammation of the gut mucosa and the potential applications of these discoveries for IBD management.